Poldark. The complete fifth season [videorecording (DVD)] - Aprahamian, Sallie; Molotnikov, Justin; Turner, Aidan, 1983-; Tomlinson, Eleanor, 1992-; Chappell, Ellise, 1993-; Graham, Winston (PBS, 2019)
It is a new century and with it comes the promise of a hopeful future, but the past casts a long shadow over Cornwall. Following the death of Elizabeth, Ross Poldark resolves to put Westminster behind him and spend more time with the people he loves. However, when an old friend emerges with a plea for help, Ross is compelled to challenge the establishment again.